Coral snakes predict the evolution of mimicry across New World snakes - Alison R. Davis Rabosky (Nature Portfolio, 2016)
Toxic and venomous species often have conspicuous warning colouration that is mimicked by harmless species. Here, Davis Rabosky et al. combine phylogenetic and biogeographic analyses to reveal that mimicry of venomous coral snakes has been a major driver of snake colour evolution in the New World.